The measurement and clinical relevance of brain atrophy in multiple sclerosis - Bermel, Robert A; Bakshi, Rohit (Lancet neurology, 2006)
Brain atrophy has emerged as a clinically relevant component of disease progression in multiple sclerosis. Progressive loss of brain tissue bulk can be detected in vivo in a sensitive and reproducible manner by MRI. Clinical studies have shown that brain atrophy begins early in the disease course. The increasing amount of data linking brain atrophy to clinical impairments suggest that irreversible tissue destruction is an important determinant of disease progression to a greater extent than can be explained by conventional lesion assessments. In this review, we will summarise the proposed mechanisms contributing to brain atrophy in patients with multiple sclerosis. We will critically discuss the wide range of MRI-based methods used to quantify regional and whole-brain-volume loss. Based on a review of current information, we will summarise the rate of atrophy among phenotypes for multiple sclerosis, the clinical relevance of brain atrophy, and the effect of disease-modifying treatments on its progression.